Empirical Models For Estimating Precipitable Water Using Advanced Tiros Operational Vertical Sounder Satellite Data Over Peninsular Malaysia - Kaura, Makama Ezekiel (2018)
Precipitable water (PW) is a highly variable, but important greenhouse gas that regulates the radiation budget of the earth. Adequate knowledge on its distribution, in space and time, is required for a better description and understanding of weather and global climate. The few existing studies in Peninsular Malaysia utilized in situ data to estimate TPW, with the consequences of oversimplifying the situation by masking the effects of local circulation and topographical difference, which are considered important in small scale weather studies. Also, the use of single meteorological parameter to estimate TPW usually undermines other parameters that may have combined effect on the column water vapour. New models based on multiple linear regression (MLR) to estimate TPW have, therefore, been proposed using homogenized climate data records derived from ATOVS onboard NOAA along with surface observations for the period 2001 – 2011. ATOVS data agreed well with radiosonde measurements, both spatially and seasonally, with correlation coefficients (